Delegated voting in decentralized autonomous organizations: a scoping review - Weidener, Lukas; Laredo, Fabio; Kumar, Kishore; Compton, Karlin (Frontiers in Blockchain, 2025)
This study presents a systematic scoping review of delegated voting (DV) in decentralized autonomous organizations (DAOs), focusing on its governance implications, implementation forms, and challenges. DV refers to a mechanism through which token holders transfer their voting rights to other participants, often called delegates, who vote on their behalf. While DV is often adopted to address low participation and mitigate the cognitive burden of direct involvement, the existing literature highlights its potential to exacerbate centralization, particularly when whales or influential networks are disproportionate. This creates tension between the intended efficiency gains of the delegation and the unintended concentration of power. Various implementation models, including off-chain platforms (e.g., Snapshot), hybrid governance architectures, and token-based delegation systems, exhibit distinct trade-offs in transparency, cost, and adaptability. Although innovations such as quadratic voting, weighted delegation constraints, and reputation-based governance show promise for improving fairness and accountability, they also face vulnerabilities, such as gaming, collusion, and high implementation complexity. To explore the diverse approaches to DV, this review organizes and synthesizes key findings from recent scholarly publications examining its implementation, risks, and governance outcomes. Synthesizing insights from 13 publications, this review identifies key governance trade-offs, implementation patterns, and risks associated with DV. It also outlines future research directions, including multi-tiered governance structures and decision-support mechanisms, to guide more inclusive and context-aware DAO governance.